2020
DOI: 10.18848/2160-1933/cgp/v10i01/19-42
|View full text |Cite
|
Sign up to set email alerts
|

Social Self-Organization and Social-Ecological Resilience in Food Systems: Lessons from Smallholder Agriculture in Kenya and Indigenous Guaraní Communities in Bolivia

Abstract: Food systems face pressures related to global environmental change and agricultural intensification that make access to productive resources difficult for many actors. Social self-organization is one of the measures taken by actors to enable them to increase their capacity to mitigate challenges and increase their influence as well as build resilience against risks. The objectives of this study were to assess the level of social self-organization in food systems, to identify forms of social self-organization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 37 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…Membership to farmer groups was significant for food security, underpinning the important role of social capital. This confirms the results of earlier studies [20,39,40] that found that membership to farmer groups matters regarding food security. Farmer groups and associations, particularly among smallholder farmers, have been found to be providers or enablers of marketing and access to financial and extension services [41].…”
Section: Discussionsupporting
confidence: 92%
“…Membership to farmer groups was significant for food security, underpinning the important role of social capital. This confirms the results of earlier studies [20,39,40] that found that membership to farmer groups matters regarding food security. Farmer groups and associations, particularly among smallholder farmers, have been found to be providers or enablers of marketing and access to financial and extension services [41].…”
Section: Discussionsupporting
confidence: 92%
“…This is an indication that smallholders may have the possibility to benefit as such from economies of scale by being organized in groups. Studies (Thomas et al, 2011;Fischer and Qaim, 2014;Mukhovi et al, 2020;Mwangi et al, 2020) have shown that smallholder farmers in developing countries like Kenya obtain economic and social benefits such as improved access to markets and market-related services, credit, information and training from group membership. With the devolution of agriculture in Kenya, we advocate for county-level government support to strengthen farmer groups.…”
Section: Discussionmentioning
confidence: 99%
“…Social-ecological resilience 23,24,[33][34][35] Resilience of the food system in terms of buffer capacity, self-organization, and the capacity for learning and adaptation…”
Section: Description Indicators Food System Activitymentioning
confidence: 99%
“…Participatory land use mapping was conducted on nine farms providing data on landscape heterogeneity 23 . The other resilience indicators were covered through 77 interviews in total: 25 smallholders; 20 pastoralists, five managers of horticultural companies; five retailers/middlemen, three wholesalers, and five restaurants; 14 organizations that deal with resilience building and risk mitigation (NGOs, a nutritional health expert, representatives of the national and county governments of Laikipia and Meru, relevant ministries, and research organizations) 24,33 . As in the case of the indicator for environmental performance, as the 100% value we took the highest value found in the sample each for Kenya and Bolivia.…”
Section: Right To Foodmentioning
confidence: 99%
See 1 more Smart Citation